Pengaruh Citra Merek Dan Kualitas Produk Terhadap Kepercayaan Pengguna Produk Smartphone Merek Evercross Di Kota Semarang - Karisna Karisna; Dewi Fatmasari (Universitas Pandanaran, 2021)
Today's cellphone is not a luxury item, but has become a daily necessity for adults and teenagers, not only for communication but for working and studying too. Competition for mobile phone products today is very tight, so manufacturers must be able to maintain consumer trust or loyalty through a brand image and product quality that is always being improved and creating new products. And The purpose of this study was to determine the effect of brand image and product quality on user trust of the Evercross smartphone brand in the city of Semarang. The results showed that the Evercoss brand image was considered good by its users. This was stated by 35% of respondents who stated that the Evercoss brand image was good. There is a significant influence between brand image on trust, which is equal to 0.406. Thus, hypothesis 1 is accepted, which means that the better the Evercoss brand image, the better the user's trust in the Evercoss smartphone. The quality of the Evercoss smartphone products is considered good. This is evidenced by the response stating that the quality of the Evercoss smartphone product is good, which is 42%. There is a significant influence between product quality on trust, which is equal to 0.280. Thus, hypothesis 2 is accepted, which means that the better the quality of the Evercoss smartphone product, the better will the user's trust in the Evercoss smartphone be. Key Word : citra merek, kualitas produk, kepercayaan